Investigation on producing silica from rice husk biomass - Uddin, M.N.; Rashid, Muhammad Mahbubur; Taweekun, J.; Techato, K.; Roy, R.; Rahman, M.A. (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2018)
Intending to contribute with the valorization of rural squanders that present transfer issues and the utilization of sustainable power sources, was looked into the rice husk burning in climatic foaming fluidized bed reactor. The technique was to assess the air overabundance impact in the pipe gases and the powder attributes. It was resolved the gases organization (CO, CO2 and NOx) and portrayed theash produced (XRD, XRF). 40%excessair advances temperatures inside the reactor around 700°C with higher change efficienciesbut declining the nebulous silica capability of the fiery debris. Opposite conduct was confirm at 128% overabundance air. The pipe gases demonstrated relative inconstancy for each working condition. In the CO case, a normal grouping of 200 ppm was found (on a dry premise of 11% O2) for air overabundance somewhere in the range of 40.0% and 82.5%.